Gymnastics in enterprises (Fiep Bulletin - online, 2015)
Pause gymnastics on the working premises certainly makes for a decrease of symptoms which are a consequence of the unilateral overloading of certain muscular tension. If it is rightly led it makes morbidity and absenteeism diminish. There can be no doubt about this.